2012
DOI: 10.2139/ssrn.2084648
|View full text |Cite
|
Sign up to set email alerts
|

Sharing Rule Identification for General Collective Consumption Models

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 40 publications
0
41
0
Order By: Relevance
“…It is simply the function that summarizes the relationship between individual preferences and household choices. In the general formulation of the collective model (Cherchye et al, 2015), the weight λ may depend on a variety of factors including outside options for the partners, wage rates, total expenditure and prices.If λ is fixed, then the collective model is equivalent to a unitary model of the household (Vermeulen, 2002). So the collective model can be seen as a generalization of the unitary model that allows λ to vary with the environment faced by the household.Cooperative models such as McElroy and Horney (1981) and Manser and Brown (1980) represent a third approach in which further structure is placed on λ, usually by being specific about fall-back options and adding axioms about the solution to the household bargaining problem, the most common of which is the Nash bargaining solution.…”
mentioning
confidence: 99%
“…It is simply the function that summarizes the relationship between individual preferences and household choices. In the general formulation of the collective model (Cherchye et al, 2015), the weight λ may depend on a variety of factors including outside options for the partners, wage rates, total expenditure and prices.If λ is fixed, then the collective model is equivalent to a unitary model of the household (Vermeulen, 2002). So the collective model can be seen as a generalization of the unitary model that allows λ to vary with the environment faced by the household.Cooperative models such as McElroy and Horney (1981) and Manser and Brown (1980) represent a third approach in which further structure is placed on λ, usually by being specific about fall-back options and adding axioms about the solution to the household bargaining problem, the most common of which is the Nash bargaining solution.…”
mentioning
confidence: 99%
“…Resource shares also depend on a pair of observed distribution factors y h : the relative wage of the woman vs. the man and the relative education level of the woman vs. the man. In other research (e.g., Cherchye et al ), these two variables have been shown to be positively correlated with women's resource shares. Finally, the resource share depends on logged relative prices, ln p j / p J .…”
Section: An Illustration With Canadian Datamentioning
confidence: 72%
“…As an implication, we allow the Hicksian market good and time spent on household production to be characterized by a public component, while time spent on leisure is modeled as purely private. 12 Data. We use household data drawn from the 2013 wave of the Panel Study of Income Dynamics (PSID).…”
Section: Empirical Application: Set-upmentioning
confidence: 99%